REGULATION OF REACTIVE POWER AND VOLTAGE IN ELECTRIC NETWORKS, AS ADDITIONAL SERVICE - Lezhniuk, Petro; Gritsiuk, Yuriy; Pirniak, Victor (Scientific Works of Vinnytsia National Technical University, 2015)
Factors of reactive power influence on technical-economic indices of electric network, have been analyzed. It is shown, that generation, transmission and reactive power regulation expenses in market conditions must be reimbursed. REFERENCES 1. Бессонов Л.А. Теоретические основы электротехники. – М.: Высшая школа, 1967. – 775 с. 2. Ілка Левінгтон. Україна – впровадження концепції оптового ринку електроенергії // Електропанорама. – 2009. – № 1–3. 3. Никитин А.А., Олефир Д.А., Франчик Е.Н. Особенности развития балансирующего рынка и рынка вспомогательных услуг в ОЭС Украины // Електропанорама. – 2010. – № 1–4. 4. Методика обчислення плати за перетікання реактивної електроенергії між енергопередавальною організацією та її споживачами (затверджена наказом Мінпаливенерго України 17.01.2002 р. за №19 і зареєстрована Міністерством юстиції України 01.02.2002 р. за №93/6381). 5. Иванов-Смоленский А.В. Электрические машины. – М.: Энергия, 1980. – 928 с. 6. Карпов Ф.Ф. Компенсация реактивной мощности в распределительных сетях. – М.: Энергия, 1975. – 184 с. 7. Веников В.А. Переходные электромеханические процессы в электрических системах. – М.: Высшая школа, 1985. – 536 с.